The cognitive toll of household air pollution: cross–sectional associations between polluting cooking fuel use, cognitive functions and brain MRI in a rural aging population from Karnataka, IndiaResearch in context - Sumedha Mitra; Manogna Sagiraju; Hitesh Pradhan; David Yao; Jayant M. Pinto; Jonas S. Sundarakumar (The Lancet Regional Health - Southeast Asia)
Summary: Background: Household air pollution (HAP) from polluting cooking fuels, a rampant issue in rural India, is suspected to be a significant modifiable risk factor for cognitive impairment; however, evidence supported by neuroimaging in this population, is lacking. Methods: Baseline cross-sectional data (n = 4145) of participants aged ≥45 years from the ongoing Centre for Brain Research-Srinivaspura Aging, Neuro Senescence, and COGnition (CBR-SANSCOG) study in a rural South Indian aging population, was utilised. HAP exposure was proxied via polluting cooking fuel or technology use (only clean vs. at least one polluting vs. only polluting cooking technology use). Global and domain-specific cognitive functioning was assessed using computerised culturally adapted test batteries. A subset (n = 994) underwent brain MRI (3T) to estimate regional brain volumes and white matter hyperintensities (WMHs) burden. Fully adjusted linear regression models were used to test the associations between HAP exposure, cognition, and brain MRI parameters. Findings: Only polluting cooking technology users had significantly lower scores in global cognition (βstd. = −0.28 [−0.44, −0.11], padj [FDR corrected p-value] = 0.002), visuospatial ability (βstd. = −0.28 [−0.48, −0.08], padj. = 0.013), and executive functions (βstd. = −0.25 [−0.44, −0.07], padj. = 0.019), whereas at least one polluting cooking technology users had lower scores in global cognition only (βstd. = −0.10 [−0.15, −0.04], padj. <0.001), compared to the clean cooking technology users. Upon sex-stratification, only female polluting cooking technology users had lower global cognitive scores (βstd. = −0.11 [−0.20, −0.03], padj. = 0.018) and lower hippocampus volumes (βstd. = −0.18 [−0.35, −0.01], p = 0.030). Interpretation: Polluting cooking technology users may be at a higher risk for cognitive impairment. Rural females, who tend to be more exposed than males, could have greater vulnerability to HAP's adverse effects on the brain. Policies promoting clean cooking fuel/technology adoption are imperative. Funding: CBR-SANSCOG study is funded by the Centre for Brain Research, India.